2022
DOI: 10.48550/arxiv.2201.00876
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quasi-Sterile Neutrinos from Dark Sectors I. BSM matter effects in neutrino oscillations and the short-baseline anomalies

Daniele S. M. Alves,
William C. Louis,
Patrick G. deNiverville

Abstract: Quasi-sterile neutrinos are a natural consequence of dark sectors interacting with the Standard Model (SM) sector via neutrino-and vector-portals. Essentially, quasisterile neutrinos are light dark sector fermions with two generic properties: (i) they mix with the active neutrinos of the SM, and (ii) they are charged under a vector mediator that couples feebly to SM matter. Various interesting phenomenological consequences result from this class of particles. In this article, we investigate one such consequenc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 100 publications
(119 reference statements)
0
4
0
Order By: Relevance
“…More recently, [148] reiterated that these tensions with long-baseline experiments occur because new matter effects generically distort the active (anti-)neutrino mixing and mass spectrum. A dark sector model with both neutrino and vector portals was then proposed in [148] that avoids these large (2) , are shown as a function of the distance traveled by neutrinos in the Earth assuming a common m 2 J = 0.1 eV 2 . The top, middle and bottom panels are for α = e, τ , and µ, respectively.…”
Section: Light Sterile Neutrino Oscillations and Non-standard Interac...mentioning
confidence: 99%
“…More recently, [148] reiterated that these tensions with long-baseline experiments occur because new matter effects generically distort the active (anti-)neutrino mixing and mass spectrum. A dark sector model with both neutrino and vector portals was then proposed in [148] that avoids these large (2) , are shown as a function of the distance traveled by neutrinos in the Earth assuming a common m 2 J = 0.1 eV 2 . The top, middle and bottom panels are for α = e, τ , and µ, respectively.…”
Section: Light Sterile Neutrino Oscillations and Non-standard Interac...mentioning
confidence: 99%
“…Recent reviews and references on active-sterile oscillation solutions to the anomalies may be found in [8,[34][35][36][37][38]. Variants on the simple vacuum oscillation solution, which use matter effects and resonant oscillations with new mediators to produce a single electron or positron in the detector may be found in [39] (vector mediator) and [40] (scalar mediator).…”
Section: The Lee and Its Resolution Via New Physics: A Post-microboon...mentioning
confidence: 99%
“…Both subsets of proposals in category a) remain in contention due to reasons described in recent work [39,[46][47][48], i.e. that MicroBooNE results disfavour but do not eliminate the possibility that LSND and MB results can be explained by i) O(eV) sterile neutrinos with active-sterile mixing and oscillations, or more generally, by ii) the presence of additional ν e in the beam.…”
Section: The Lee and Its Resolution Via New Physics: A Post-microboon...mentioning
confidence: 99%
See 1 more Smart Citation